Anticoagulation After Stroke in Patients With Atrial Fibrillation: To Bridge or Not With Low-Molecular-Weight Heparin?. Issue 8 (August 2019) - Altavilla, Riccardo; Caso, Valeria; Bandini, Fabio; Agnelli, Giancarlo; Tsivgoulis, Georgios; Yaghi, Shadi; Furie, Karen L.; Tadi, Prasanna; Becattini, Cecilia; Zedde, Marialuisa; Abdul-Rahim, Azmil H.; Lees, Kennedy R.; et al.
Abstract : Background and Purpose—: Bridging therapy with low-molecular-weight heparin reportedly leads to a worse outcome for acute cardioembolic stroke patients because of a higher incidence of intracerebral bleeding. However, this practice is common in clinical settings. This observational study aimed to compare (1) the clinical profiles of patients receiving and not receiving bridging therapy, (2) overall group outcomes, and (3) outcomes according to the type of anticoagulant prescribed. Methods—: We analyzed data of patients from the prospective RAF and RAF-NOACs studies. The primary outcome was defined as the composite of ischemic stroke, transient ischemic attack, systemic embolism, symptomatic cerebral bleeding, and major extracerebral bleeding observed at 90 days after the acute stroke. Results—: Of 1810 patients who initiated oral anticoagulant therapy, 371 (20%) underwent bridging therapy with full-dose low-molecular-weight heparin. Older age and the presence of leukoaraiosis were inversely correlated with the use of bridging therapy. Forty-two bridged patients (11.3%) reached the combined outcome versus 72 (5.0%) of the nonbridged patients ( P =0.0001). At multivariable analysis, bridging therapy was associated with the composite end point (odds ratio, 2.3; 95% CI, 1.4–3.7; P <0.0001), as well as ischemic (odds ratio, 2.2; 95% CI, 1.3–3.9; P =0.005) and hemorrhagic (odds ratio, 2.4; 95% CI, 1.2–4.9; P =0.01) end points separately. Conclusions—: Our findings suggest that patients receiving low-molecular-weight heparin have a higher risk of early ischemic recurrence and hemorrhagic transformation compared with nonbridged patients. Abstract : Supplemental Digital Content is available in the text.